THE CONNECTION BETWEEN CENTRAL OBESITY AND THE DISTRIBUTION OF SPINAL ANESTHESIA IN FEMALE PATIENTS - Nematulloev Tukhtasin Komiljonovich; Dusmatov Muhsin Komil o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Central obesity might influence the spread of spinal anesthesia in female patients. In a study, fifty-seven female patients undergoing spinal anesthesia were divided into either a central obesity group or a non-central obesity group. Following the induction of spinal anesthesia, several parameters were evaluated: maximal sensory blockade (primary outcome), time to maximal sensory block, maximum motor block, time to maximum motor block, time to L2 regression, and time to reach Bromage scale 0. Multiple linear regression analyses revealed that maximal sensory blockade was associated with central obesity (P = .004). Therefore, central obesity is linked to a more extensive spread of spinal anesthesia in female patients.